Vitamin D status and risk of infections after liver transplantation in the Swiss Transplant Cohort Study. (3rd September 2018) - Schreiber, Peter W.; Bischoff‐Ferrari, Heike A.; Boggian, Katia; van Delden, Christian; Enriquez, Natalia; Fehr, Thomas; Garzoni, Christian; Hirsch, Hans H.; Hirzel, Cédric; Manuel, Oriol; Meylan, Pascal; Saleh, Lanja; et al.
Summary: Increasing evidence indicates a role of vitamin D in the immune system affecting response to infections. We aimed to characterize the role of vitamin D status, i.e. deficiency [25‐OH vitamin D (25‐OHD) <50 nmol/l] and no deficiency (25‐OHD ≥50 nmol/l) in incident infections after liver transplantation. In 135 liver transplant recipients, blood samples drawn at time of liver transplantation and 6 months afterwards were used to determine 25‐OHD levels. Incident infections episodes were prospectively collected within the Swiss Transplant Cohort Study database. Poisson regression was applied to address associations between vitamin D status and incident infections. Vitamin D deficiency was common at time of transplantation and 6 months afterwards without a significant change in median 25‐OHD levels. In univariable analyses, vitamin D deficiency was a risk factor for incident infections in the first 6 months post‐transplant incidence rate ratio (IRR 1.52, 95% CI 1.08–2.15, P = 0.018) and for bacterial infections occurring after 6 up to 30 months post‐transplant (IRR 2.29, 95% CI 1.06–4.94, P = 0.034). These associations were not detectable in multivariable analysis with adjustment for multiple confounders. Efforts to optimize vitamin D supplementation in liver transplant recipients are needed. Our data question the role of vitamin D deficiency in incident infections.